Increased of IL-18 levels are associated with periodontitis: a systematic review and meta-analysis - Alarcón-Sánchez, Mario Alberto; Romero-Castro, Norma Samanta; Becerra-Ruiz, Julieta Sarai; Romero-Servin, Selenne; Heboyan, Artak (BMC oral health, 2024)
The presence of a polymicrobial dysbiotic film in direct and constant contact with periodontal tissues initiates the host immune response. Interleukin 18 (IL-18) triggers up-regulates the production of other proinflammatory cytokines (TNF-α, IL-1β, IL-6), creating a vicious cycle that expands the inflammatory and destructive process in the periodontal tissue. A systematic review and meta-analysis was carried out with the main propose to investigate IL-18 expression in different biological samples from subjects with chronic periodontitis. The protocol followed PRISMA guidelines and was registered in Open Science Framework (OSF): https://doi.org/10.17605/OSF.IO/BS9GM . A digital search was conducted in the databases PubMed, ScienceDirect, Google Scholar, Web of Science and Dentistry & Oral Sciences Source databases were consulted from March 15th, 2005 to February 10th, 2023. Study quality was assessed using the JBI tool for cross-sectional studies and clinical trials. A meta-analysis was performed using a random/fixed effects model to evaluate the concentration of IL-18 in serum, plasma, saliva, gingival tissue and GCF of exposure group compared to control group. The search strategy provided a total of 3,156 articles, of which 18 investigations met the inclusion criteria and 15 articles were quantitatively analyzed. The total number of patients studied was 1,275 (682 cases and 593 controls). The meta-analysis revealed significantly elevated IL-18 levels of serum, saliva and GCF of subjects with chronic periodontitis compared to healthy subjects (Serum: SMD = 62.73, 95%CI: 25.43-100.03, Z = 3.29, p = 0.001*; Saliva: SMD = 243.63, 95%CI: 8.68-478.59, Z = 2.03, p = 0.042*; GCF: SMD = 150.26, 95%CI: 56.86-243.66, Z = 3.15, p = 0.02*). IL-18 levels in serum, saliva and GCF could have the potential to be used as complementary diagnostic tools to the clinical and radiographic parameters in subjects with periodontitis.